U.S. Arctic security policy: North American Arctic strategies, Russian hubris and Chinese ambitions - Michael Paul (Stiftung Wissenschaft und Politik (SWP), 2023)
Unlike his predecessors, US President Joe Biden made important decisions early in his term to enable better coordination of US Arctic policy. This includes foremost the National Strategy for the Arctic Region that was published later than planned as a result of Russia's war of aggression, which destroyed the few remaining hopes for cooperation and made the Arctic a security policy issue. Alaska, as the northernmost American state, is naturally at the centre of US Arctic policy, which increasingly also must take Chinese activities into consideration. Most recently, in September 2022, the U.S. Coast Guard (USCG) detected Chinese and Russian warships off Alaska. Currently, only one US icebreaker is continuously available in the Arctic theatre with the mission to protect sovereignty in the Arctic Ocean and monitor ice-covered areas. Alaska is also the very same US state that the recent Chinese spy balloon flew over, which was eventually shot down in February 2023. After decades of scant attention, is the Arctic now finally becoming the object of a more engaged US security policy?
Keywords: 320; Joe Biden; US Arctic policy; National Strategy for the Arctic Region; China; Russia; U.S. Coast Guard (USCG); Alaska